Cover Feature: Borane Adducts of Aromatic Phosphorus Heterocycles: Synthesis, Crystallographic Characterization and Reactivity of a Phosphinine‐B(C6F5)3 Lewis Pair (Chem. Eur. J. 7/2022). Issue 7 (22nd January 2022) - Lin, Jinxiong; Wossidlo., Friedrich; Coles, Nathan T.; Weber, Manuela; Steinhauer, Simon; Böttcher, Tobias; Müller, Christian
Abstract : The first crystallographically characterized phosphinine–borane adduct mimics frustrated Lewis‐pair reactivity. In the presence of alkynes, alkenes and esters, a facile conversion to novel phosphinine‐based species is achieved even at room temperature. Our results provide fascinating new perspectives for the future, particularly with respect to the activation of small molecules. More information can be found in the Research Article by T. Böttcher, C. Müller et al. (DOI: 10.1002/chem.202104135 ).